2015
DOI: 10.1074/jbc.m115.657346
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon-induced Transmembrane Proteins, IFITM1, IFITM2, and IFITM3 Inhibit Hepatitis C Virus Entry

Abstract: Background: Interferon-induced transmembrane (IFITM) proteins limit a broad range of RNA viruses. Results: Tyrosine phosphorylation of IFITM2 and IFITM3, and S-palmitoylation of the IFITM proteins, are crucial for antihepatitis C virus (HCV) activity. Conclusion: IFITM2 and IFITM3 are able to limit HCV infection by targeting the late entry stages of the virus. Significance: IFITM proteins inhibit HCV at early and late stages of entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 47 publications
11
119
0
5
Order By: Relevance
“…S5 and S6). Our results are consistent with previous IFITM mutagenesis and antiviral activity studies (21,22,27,32,35), but demonstrates that antiviral activity is directly correlated to S-fatty acylation levels and that dually S-fatty acylated IFITM3 at Cys72 and Cys105 is likely the most active isoform in mammalian cells (Fig. S9).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…S5 and S6). Our results are consistent with previous IFITM mutagenesis and antiviral activity studies (21,22,27,32,35), but demonstrates that antiviral activity is directly correlated to S-fatty acylation levels and that dually S-fatty acylated IFITM3 at Cys72 and Cys105 is likely the most active isoform in mammalian cells (Fig. S9).…”
Section: Discussionsupporting
confidence: 82%
“…4). Although previous studies have suggested that mutation of these conserved Cys residues may partially affect the localization or trafficking of IFITMs in mammalian cells (21,22,27,32), our quantitative immunofluorescence analysis suggest that site-specific S-fatty acylation may regulate more subtle functions of IFITM3 beyond lysosomal targeting (Figs. S7 and S8), such as protein-protein interactions (33,34) or membrane tethering, but which awaits more detailed biochemical or biophysical studies.…”
Section: Discussionmentioning
confidence: 93%
“…Unexpectedly, preS1 treatment also induced the expression of genes involved in innate immunity, such as IFNα responses and the Jak/Stat-signaling pathway (Table 1; Figure 4A). Interestingly, IFITM2 and IFITM3 , which encode two restriction factors targeting HCV entry (Narayana et al., 2015), were among the preS1-induced genes (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…23 IFITM proteins have been reported to be regulated by palmitoylation and ubiquitination, for example. 24, 25 This might explain our finding that the increase in IFITM1 protein both in control and S100A6 knockdown cells is partially overcome by short-term VEGF-A treatment. To test the impact of increased IFITM1 protein levels, we conducted a dual S100A6/IFITM1 siRNA-mediated knockdown in HUVECs.…”
Section: Resultsmentioning
confidence: 86%